2005
DOI: 10.1200/jco.2005.07.097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exemestane Administered for 2 Years Versus Placebo on Bone Mineral Density, Bone Biomarkers, and Plasma Lipids in Patients With Surgically Resected Early Breast Cancer

Abstract: Exemestane modestly enhanced bone loss from the femoral neck without significant influence on lumbar bone loss. Except for a 6% to 9% drop in plasma high-density lipoprotein cholesterol, no major effects on serum lipids, coagulation factors, or homocysteine were recorded. Bone mineral density should be assessed according to the US Preventive Services Task Force guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
148
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(154 citation statements)
references
References 43 publications
2
148
2
2
Order By: Relevance
“…The increase in LDL-C may therefore be at least partially explained by the loss of the positive action of tamoxifen. The decrease in HDL-C in the exemestane group is in line with previous studies, and may be explained by a direct action of exemestane and/or by the interruption of tamoxifen therapy (Atalay et al, 2004;Lonning et al, 2005;Markopoulos et al, 2005;Esteva and Hortobagyi, 2006). The Intergroup Exemestane Study found a trend toward more frequent myocardial infarction in patients treated with exemestane than in those treated with tamoxifen (Coombes et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…The increase in LDL-C may therefore be at least partially explained by the loss of the positive action of tamoxifen. The decrease in HDL-C in the exemestane group is in line with previous studies, and may be explained by a direct action of exemestane and/or by the interruption of tamoxifen therapy (Atalay et al, 2004;Lonning et al, 2005;Markopoulos et al, 2005;Esteva and Hortobagyi, 2006). The Intergroup Exemestane Study found a trend toward more frequent myocardial infarction in patients treated with exemestane than in those treated with tamoxifen (Coombes et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…One of these preclinical studies also evaluated the nonsteroidal AI letrozole, but in contrast, found no benefit of letrozole on bone or lipid profiles (16). In a clinical study investigating the effects of 2 years of exemestane on bone compared with placebo without prior tamoxifen therapy in patients with surgically resected breast cancer at low risk for recurrence, exemestane did not enhance BMD loss in lumbar spine and only modestly enhanced BMD loss in the femoral neck compared with the placebo group (17). Interestingly, in this study, exemestane promoted bone metabolism by increasing levels of both bone resorption and formation markers (17).…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical study investigating the effects of 2 years of exemestane on bone compared with placebo without prior tamoxifen therapy in patients with surgically resected breast cancer at low risk for recurrence, exemestane did not enhance BMD loss in lumbar spine and only modestly enhanced BMD loss in the femoral neck compared with the placebo group (17). Interestingly, in this study, exemestane promoted bone metabolism by increasing levels of both bone resorption and formation markers (17). However, a clear-cut advantage of exemestane versus the nonsteroidal AIs on bone safety has not been shown in humans, possibly because all other clinical studies compared the AI to tamoxifen (9,12,18) or the AI to placebo with prior tamoxifen therapy (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…These include patients who do not have pathological prognostic factors which predict a higher and earlier relapse rate, such as higher histological grade, presence of vascular invasion, tumour size and number of positive axillary nodes [24], and biological molecular markers such Cerb2, Ki67, CYP-2D6, level of oestrogen receptor positivity and progesterone receptor negativity [24,25]. However, even if patients have a good prognosis, patients may also be better off on anastrozole if they have a history of thromboembolic disease or risk of uterine carcinoma [24][25][26]. More recently, the roles played by quality of life, tolerance and patient preference also have important implications on the choice of adjuvant drug [5].…”
Section: Discussionmentioning
confidence: 99%